Pengaruh Pijat Punggung Terhadap Tekanan Darah Pada Pasien Hipertensi - Ardian Syah (Institut Citra Internasional, 2021)
Hypertension is a challenge for global health because of its high prevalence. Research studies on efforts for hypertension sufferers continue to be developed, one of which is non-pharmacological therapy, namely back massage. The purpose of this study was to determine the effect of back massage on blood pressure in hypertension patients. This research design used a quasi-experimental with a pretest-posttest control group. A sample of 54 respondents was divided into two groups. Group 1 intervention was given back massage and standard drug therapy, group 2 control received only standard drug therapy. The results of the analysis of the research conducted by Paired t-test and Wilcoxon back massage showed a significant value on the status of systolic and diastolic blood pressure with a value of p-value = <0.05. The Mann Whitney test shows that there is a significant difference in the systolic status, p-value = <0.05 and there is no significant difference in the status of Diastolic blood pressure with p-value => 0.05. The conclusion in this study that backs massage can statistically reduce the status of systolic and diastolic blood pressure in hypertension patients.